2022
DOI: 10.1111/tpj.16007
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome‐level genome of female ginseng (Angelica sinensis) provides insights into molecular mechanisms and evolution of coumarin biosynthesis

Abstract: SUMMARY Coumarins are natural products with important medicinal values, and include simple coumarins, furanocoumarins and pyranocoumarins. Female ginseng (Angelica sinensis) is a renowned herb with abundant coumarins, originated in China and known for the treatment of female ailments for thousands of years. The molecular basis of simple coumarin biosynthesis in A. sinensis and the evolutionary history of the genes involved in furanocoumarin biosynthesis are largely unknown. Here, we generated the first chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 94 publications
6
12
0
Order By: Relevance
“…S6 to S8). Consistent with the previous studies ( 37 ), we only detected one whole-genome duplication (WGD) event shared by the subfamily Apioideae and did not observe any recent specific WGD event for L. chuanxiong (figs. S6 and S9).…”
Section: Resultssupporting
confidence: 92%
“…S6 to S8). Consistent with the previous studies ( 37 ), we only detected one whole-genome duplication (WGD) event shared by the subfamily Apioideae and did not observe any recent specific WGD event for L. chuanxiong (figs. S6 and S9).…”
Section: Resultssupporting
confidence: 92%
“…This genomic evolutionary feature is particularly evident in the study of medicinal plants. For instance, in the genome of Angelica sinensis , genes involved in the biosynthesis of furanocoumarins have independently evolved in the families Moraceae, Fabaceae, Rutaceae, and Apiaceae after the ζ and ε WGD [ 110 ]. Arctium lappa retains specific genes that involved in cellulose metabolism, which may play an important role in the formation of cell walls in this plant [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apiaceae species have always played an important role in socio-economic and human life, among which Angelica sinensis, Bupleurum chinense, Centella asiatica and O. javanica are medicinal plants (Lu and Li, 2019;Sun et al, 2020;Liu et al, 2022), as well as Apium graveolens, Coriandrum sativum and D. carota are vegetables (Fox et al, 2022). Previous studies have shown that the Ks peak of the paralogous genes in five Apioideae species, including Daucus carota, Oenanthe javanica, A. sinensis, C. sativum and A. graveolens, corresponded to a recent WGD (whole genome duplication) event, possibly specific in Apioideae instead of Mackinlayoideae (Han et al, 2022). A variety of pathogens are known to be capable of infecting Apiaceae plants and causing economic losses (Fox et al, 2022).…”
Section: Introductionmentioning
confidence: 99%